1969
DOI: 10.1126/science.166.3911.1424
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Smoke Toxicity: Loss of Human Oral Leukocyte Function and Fluid-Cell Metabolism

Abstract: The human mouth has been utilized as a new and significant in vivo open bioassay system for tracing undesirable substances present in tobacco smoke, in an exact milieu where the smoking "problem" begins and must be dealt with directly. The associated in vitro closed test systems described herein have provided new, sensitive bioassays that help to explain the in vivo effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 12 publications
1
39
0
Order By: Relevance
“…It is clear from previous studies that the chemotaxis and the phagocytic ability of neutrophils in peripheral blood or saliva are lowered [32,33], while the production of reactive oxygen species is increased in smokers [34,35]. It was also reported that smoking increases PGE 2 , neutrophil elastase [36] and TNF-a levels.…”
Section: Discussionmentioning
confidence: 93%
“…It is clear from previous studies that the chemotaxis and the phagocytic ability of neutrophils in peripheral blood or saliva are lowered [32,33], while the production of reactive oxygen species is increased in smokers [34,35]. It was also reported that smoking increases PGE 2 , neutrophil elastase [36] and TNF-a levels.…”
Section: Discussionmentioning
confidence: 93%
“…Polymorphonuclear leukocytes from the peripheral blood of smokers exhibit depressed migration and chemotaxis compared with PMNs from nonsmokers (Noble & Penny, 1975;Corberand et al, 1979). The motility and chemotaxis of PMNs are depressed in the oral cavity of smokers compared with nonsmokers (Eichel & Shahrik, 1969;Noble & Penny, 1975). The whole cigarette smoke, its gas phase and the water-soluble fraction are potent inhibitors of PMN chemotaxis (Bridges et al, 1977).…”
Section: Cell-mediated Immune Responsesmentioning
confidence: 99%
“…Oceanogr. 3, 448 (1973 smoking include reduced early phase of particle clearance (5), increased closing volume (6), increased airway resistance (7), and toxic effects on oral leukocytes (8). We now report that in hamsters inhaled cigarette smoke recruits polymorphonuclear (PMN) leukocytes to airway lumens from trachea to terminal bronchioles.…”
mentioning
confidence: 99%